Organizational Intelligence: Ontological Modeling of Skills - Daoudi, Najima; Nabigh, Majda; Hilal, Imane; Rahimi, Hasnae; Atiki, Fatima Zahra (International Journal of Advanced Corporate Learning (iJAC), 2020)
In both the private and public sectors, human resource management processes face considerable challenges in terms of skills management within organizations. In fact, during the recruitment process, it is difficult to find the right profile for certain functions. To cope with this constraint and thus streamline this process, organizations tend to implement intelligent management of jobs and skills. Most systems of matching a job with a profile face the difficulty of developing and maintaining resources specific to each field. In view of this, ontologies are not only a tool for professional management and strategic management of human resources, but they also make it possible to base the relationship between the couple job / profile. Thus, we propose a construction approach of three ontologies that will play a key role in knowledge management in the context of the Secrétariat Chargé De L’eau but which remains valid for later use in broader contexts.